Time-Use and Subjective Well-Being: Is Diversity Really the Spice of Life? - Naomi Friedman-Sokuler; Claudia Senik (Institute of Labor Economics (IZA), 2023)
Using the American and the French time-use surveys, we examine whether people have a preference for a more diversified mix of activities, in the sense that they experience greater well-being when their time schedule contains many different activities rather than is concentrated on a very small number. This could be due to decreasing marginal utility, as is assumed for goods consumption, if each episode of time is conceived as yielding a certain level of utility per se. With returns to specialization, people would then face a trade-off between efficiency and diversity in choosing how to allocate time. We examine these issues and investigate potential gender differences, considering both instantaneous feelings and life satisfaction.
Keywords: I31; J22; 330; time allocation; time-use diversity; subjective well-being; life satisfaction; momentary utility; gender